Engaging participatory mapping for co-management and spatial depiction of nature’s contributions to people in the Portuguese biosphere reserves - Miguel Moreira; Luciana Frazão; Jarrod Cusens; Paula Castro; António C. Gouveia; António Alves da Silva; Sara H. Santos; Inger E. Måren; Joana Alves; Helena Freitas (Ecosystems and People)
UNESCO Biosphere Reserves (BRs) are pivotal for studying and fostering sustainable interactions between people and nature. In this study, a public participatory geographical information system (PPGIS) approach was employed targeting key stakeholders across the 12 Portuguese BRs, to map their place-based perception over Nature’s Contributions to People (NCP). Stakeholders actively mapped NCP within their BRs, highlighting Habitat creation and maintenance (NCP 1), Physical and psychological experiences (NCP 16), and Supporting identities (NCP 17), underscoring the significance of the territories’ natural and cultural values. Through our analysis, we identified NCP hotspots, pinpointing the most valued areas for conservation or restoration efforts. Zonation analysis within BRs was also assessed, revealing the perceived effectiveness of the different BR zones by stakeholders. Although our study did not quantify NCP supply through biophysical data, it provided valuable insights into non-material NCP from key stakeholders’ perspectives, as well as place-based perceptions of regulating and material NCP provision. We outline that PPGIS may serve as a useful GIS-based decision support system, offering a comprehensive assessment of NCP, especially for cultural values which are not easily quantified by remote methods. Participatory approaches such as PPGIS may play a crucial role in BR governance, enhancing sustainability and equity by integrating key stakeholders’ perceptions into land use planning. Our study’s findings may contribute on the actionable knowledge advance for sustainable management practices in Portuguese BRs by incorporating stakeholder perspectives, fostering improved co-management practices, and promoting the conservation and enhancement of their ecological and cultural heritage.